IDENTIFICATION AND ANALYSIS OF MECA GENE IN MASTITIS MILK SAMPLES COLLECTED FROM FIELD CONDITIONS IN TAMIL NADU (INDIA) - G. Sathish; Kurunchi C. Divya; E. Hemakumar; K. Murugan; A. Stalin Vedamanickam; G. Sathiyapriya (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Antibiotic resistance is common problem in the treatment of bovine mastitis nowadays. Detection of methicillin resistant  Staphylococcus aureus (MRSA) is community associated between environment and animals. mecA gene is major one of staphylococcal cassette chromosome mec (SCCmec) elements in acquiring methicillin resistance. Here 55 mastitis milk samples collected from Tiruvallur district were screened for Staphylococcus spp. S. aureus, S. epidermidis and S. saprophyticus were confirmed by isolation and differentiation using coagulase test and novobiocin disc sensitivity. They were further confirmed by species specific PCR. Of these 31 isolates, 5 S. aureus, 2 S. epidermidis and 1 S. saprophyticus showed positive for mecA. Phylogenetic analysis of mecA gene sequences of methicillin resistant isolates formed a group with European and US isolates. Hence further research and control is necessary for extensive spread of mecA gene in environment.